2022
DOI: 10.1177/09612033221146700
|View full text |Cite
|
Sign up to set email alerts
|

Interferon-gamma (IFN-γ) intronic variant (rs2430561) is a risk factor for systemic lupus erythematosus: Observation from a meta-analysis

Abstract: Background The role of interferon-gamma (IFN-γ) in autoimmune disorders has been well documented. Elevated levels of IFN-γ are observed in rheumatoid arthritis (RA) and systemic lupus erythematosus (SLE) and are linked with disease severity. Single nucleotide polymorphism in the intronic region of the IFN-γ gene (+874 T>A rs2430561) has been associated with susceptibility to the development of RA and SLE; however, the reports remained contradictories. We conducted a meta-analysis using earlier published art… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 42 publications
(73 reference statements)
1
6
0
1
Order By: Relevance
“…7,8 A recent metaanalysis showed that almost one third of patients with SLE have migraine. 9 Katsiari et al showed that migraine prevalence in patients with SLE did not differ compared to those without SLE, and they suggested that the increased migraine prevalence found previously could have been due to methodological weaknesses. 10 The current evidence is primarily based on observational studies and suffers from shortcomings such as reverse causality, small sample sizes, and confounding factors (such as the distributions of gender and age).…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations
“…7,8 A recent metaanalysis showed that almost one third of patients with SLE have migraine. 9 Katsiari et al showed that migraine prevalence in patients with SLE did not differ compared to those without SLE, and they suggested that the increased migraine prevalence found previously could have been due to methodological weaknesses. 10 The current evidence is primarily based on observational studies and suffers from shortcomings such as reverse causality, small sample sizes, and confounding factors (such as the distributions of gender and age).…”
Section: Introductionmentioning
confidence: 94%
“…Previous studies have shown a higher prevalence of migraine in patients with SLE compared to the general population, suggesting a possible link between these two conditions 7,8 . A recent meta‐analysis showed that almost one third of patients with SLE have migraine 9 . Katsiari et al.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Certain conditions are associated with primary or secondary headaches, including thyroid disease, systemic lupus erythematosus, polycystic ovarian syndrome, and joint hypermobility disorders. [58][59][60][61] SOCIAL HISTORY. A standard social history reveals information about smoking, alcohol consumption, drug use, employment type and status, physical activity, and the home environment.…”
Section: Key Pointsmentioning
confidence: 99%
“…A subsequent case–control study confirmed that the incidence of migraine was higher in patients with SLE than in healthy controls (Tjensvoll et al., 2011). In addition, a recent meta‐analysis showed that approximately one‐third of patients with SLE worldwide suffered from migraine and that the incidence of migraine was higher in patients with SLE than in healthy controls (Sarangi et al., 2023).…”
Section: Introductionmentioning
confidence: 99%